Selective Hydrogenation of Crotonaldehyde on SiO2‐Supported Pt Clusters: A DFT Study. Issue 10 (24th July 2022) - Song, Yang; Hu, Chaoquan; Li, Chang; Ma, Meng
Abstract: The selective hydrogenation of crotonaldehyde has gained considerable attention owing to its industrial applications for producing fine chemicals. Understanding the hydrogenation mechanism from density functional theory (DFT) calculations can provide insights for designing catalysts with high selectivities toward the target products. Among contemporary theoretical investigations of the hydrogenation, the calculated selectivities are not in agreement with the experimental results. Herein, a SiO2 ‐supported Pt nanocluster is developed, and it is used to investigate the selective hydrogenation of crotonaldehyde. The nanocluster model is used to obtain free energy barriers from DFT calculations, and these are used to build a microkinetic model. The theoretical selectivity values for the products are in agreement with the experimental results. According to the density of state analysis, this is directly attributed to the more accurate d‐band width from the Pt cluster. The contribution of each step to the final product is identified and can be used to intensify the process of generating the target product. Abstract : Investigating the hydrogenation mechanism of crotonaldehyde on a Pt cluster can be a more accurate representation in real‐life scenarios. Through the microkinetic model, the most favored pathway and the corresponding rate‐limiting step for the target product formation is identified. Moreover, the formation rates of the final products are calculated, and the results are highly consistent with the experimental results.